Twisting in the shadows: Omental torsion revealed on CT imaging - S Reddy, Chethana; Vignesh, Vettri; A, Baskar (Journal of Neonatal Surgery, 2025)
Omental torsion, a rare cause of acute abdomen with an incidence of 0.0016% to 0.37%, can be primary or secondary; the latter is more common and often associated with hernial sacs, wounds, or surgical scarring. We report the case of a 30-year-old male with a long-term right inguinal hernia who presented with severe abdominal pain for four days. Examination revealed tenderness and guarding in the right lumbar and iliac regions with mild leukocytosis on laboratory tests. Abdominal ultrasonography, CT, and MRI confirmed a large right inguinal hernia, with omental torsion and infarction. The patient underwent surgical resection of the necrotic omentum and open mesh hernioplasty, with uneventful postoperative recovery. Accurate diagnosis of omental torsion is challenging due to nonspecific clinical signs, and imaging modalities such as CT and MRI are crucial for proper diagnosis and treatment, as well as for excluding other gastrointestinal disorders with similar symptoms.